Low-shrinkage ultra-high performance concrete and preparation method thereof

Mineral blends are prepared by co-firing high-aluminum solid waste and calcium oxide, and combined with other components, the shrinkage problem of ultra-high performance concrete is solved, compressive strength and volume stability are improved, solid waste resources are utilized, and solid waste resources are reduced. Production costs and environmental pollution.

CN119219379APending Publication Date: 2024-12-31SOUTHEAST UNIV +4
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310777164.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing ultra-high performance concrete causes large concrete shrinkage when the amount of cement and fume is used, hindering its promotion and application, and failing to effectively utilize solid waste, increasing production and construction costs and environmental pollution.

Method used

The mineral blend is prepared by co-fired high-aluminum solid waste and calcium oxide at 800-900℃ and combined with polycarboxylic acid water reducer, calcium oxide expansion agent, citric acid, quartz sand and fine steel fibers , by replacing cement and silica fume with a large proportion of high-aluminum solid waste, the particle grading and reaction activity of cementitious materials are optimized, and chemical shrinkage is reduced.

Benefits of technology

The compressive strength of low-shrinkage ultra-high performance concrete is improved, reducing production and construction costs, and providing a comprehensive utilization method of solid waste resources, improving the microstructure and mechanical properties of concrete, and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004309753310000021
    Figure BDA0004309753310000021
  • Figure BDA0004309753310000031
    Figure BDA0004309753310000031
  • Figure BDA0004309753310000081
    Figure BDA0004309753310000081
Patent Text Reader

Abstract

The invention discloses low-shrinkage ultra-high performance concrete and a preparation method thereof, and belongs to the technical field of concrete. The shrinkage ultra-high performance concrete is prepared from the following components in parts by mass: 100 parts of cement, 25 to 100 parts of mineral admixture, 2.1 to 3.5 parts of high-performance water reducing agent, 5 to 10 parts of expanding agent, 0.12 to 0.2 part of thickening time control agent, 2.5 to 4 parts of reinforcing agent, 100 to 160 parts of sand, 1.5 to 3 parts of fiber and 18 to 30 parts of water, the mineral admixture is a product obtained by cofiring the high-aluminum solid waste and CaO at 800-900 DEG C and then carrying out shock cooling treatment. The low-shrinkage ultra-high-performance concrete has excellent compressive strength and tensile property, meanwhile, a large proportion of high-aluminum solid waste replaces part of cement and all silica fume in existing ultra-high-performance concrete, large chemical shrinkage caused by the cement and the silica fume in the hydration reaction process is greatly reduced, and the volume stability of a matrix is improved. A large amount of solid hazardous waste with high aluminum oxide content is used, so that the production and construction cost is reduced, and meanwhile, a method for comprehensively utilizing solid hazardous waste resources is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of concrete, and in particular relates to a low-shrinkage ultra-high performance concrete and a preparation method thereof. Background Art

[0002] With the continuous advancement of large-scale engineering construction, ultra-long, ultra-high-rise, ultra-span, and ultra-large structures are constantly emerging. This new type of civil engineering structure places new and higher demands on the performance and function of materials, and there is an urgent need to solve the key technical problems of functional design and performance improvement. The use of solid waste in UHPC reduces the cement content per unit volume, changes the effective water-cement ratio within the system, greatly promotes cement hydration within UHPC, optimizes the microstructure, and improves the volume stability and mechanical properties of the system. In the long run, the use of solid waste reduces production and construction costs, reduces the negative environmental effects of cement production and construction, and achieves sustainable development. This is also the future development trend of ecological green ultra-high performance concrete.

[0003] my country is the world's largest producer and consumer of raw coal, raw aluminum and calcium carbide. It produces hundreds of millions of tons of coal gangue, millions of tons of solid and hazardous waste aluminum ash and waste cathode carbon blocks, and tens of millions of tons of calcium carbide slag every year. Improper handling often causes serious environmental pollution.

[0004] Patent CN113321467B discloses an internally cured low-shrinkage lightweight aggregate ultra-high performance concrete and a preparation method thereof. Fly ash and coal gangue are used to prepare lightweight, high-strength ceramic sand, which is used as a lightweight aggregate for ultra-high performance concrete. The drying shrinkage of the lightweight aggregate ultra-high performance concrete can be effectively reduced by compounding modified ceramic sand, an expansive agent, and steel fiber. However, the initial material processing process is relatively complex, and the reduction in shrinkage mainly relies on compounding with an expansive agent, resulting in a relatively high cost.

[0005] Patent CN114455907A discloses a lightweight, low-shrinkage, ultra-high-performance concrete and its preparation method. The lightweight aggregate, ceramic sand, is prepared by drying, cutting, sintering, and screening fly ash, gangue, and shale according to a specific ratio. The pre-wetted ceramic sand is then pre-soaked. A low level of fly ash is added to optimize performance, improve homogeneity, and reduce shrinkage. The initial raw material processing is complex, the solid waste content in the formulation is low, and the performance benefits of a high solid waste content are not considered.

[0006] Patent CN113716915B discloses a sprayed ultra-high performance concrete for corrosion protection and reinforcement. It utilizes a multi-component particle size compounding method to optimize particle grading and increase packing density. Chemical admixtures are used to improve workability and early strength. The internal curing effect of lightweight aggregates such as gangue is used to enhance later strength and reduce autogenous shrinkage. This method is complex and does not consider the performance development of ultra-high performance concrete at high dosages. Summary of the Invention

[0007] Existing ultra-high-performance concrete (UHPC) uses large amounts of cement and silica fume, resulting in significant concrete shrinkage and other issues, which seriously hinder its promotion and application. To address these issues, the present invention provides a low-shrinkage UHPC and a method for preparing it. This low-shrinkage UHPC not only exhibits superior compressive strength and low shrinkage, but also utilizes a large amount of solid hazardous waste with a high alumina content, reducing production and construction costs while providing a method for the comprehensive utilization of solid hazardous waste resources. Furthermore, a method for treating solid waste containing metallic aluminum and aluminum nitride is proposed, offering a new approach to treating such hazardous waste.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0009] A low-shrinkage ultra-high performance concrete, the raw materials for its preparation include the following components in parts by mass:

[0010]

[0011]

[0012] The mineral admixture is a product of co-firing high-aluminum solid waste and CaO at 800-900° C. and then undergoing quenching treatment.

[0013] The high-aluminum solid waste is a mixture of secondary aluminum ash and one or more of coal-fired power plant bottom ash, high-aluminum industrial waste slag, and coal gangue slag, and the secondary aluminum ash accounts for no less than 30% of the total mass of the high-aluminum solid waste.

[0014] The specific preparation method of the mineral admixture is as follows: mixing high-aluminum solid waste and CaO and co-firing at 800-900°C for 4-5 hours, taking it out and placing it in the air to quench and cool it to room temperature, and then grinding it to an average particle size of no more than 5 μm and a specific surface area of ​​no less than 6000 m 2 / kg, and the mineral admixture is obtained.

[0015] The mass ratio of the high-aluminum solid waste to CaO is 1.6-2.5:1.

[0016] Furthermore, the cement is ordinary Portland cement with a strength grade of 42.5 or above.

[0017] Furthermore, the high-performance water-reducing agent is a polycarboxylic acid water-reducing agent with a water reduction rate of ≥35%.

[0018] Furthermore, the expansion agent is a calcium oxide expansion agent.

[0019] Furthermore, the coagulant is at least one of citric acid or sodium citrate, which is mainly used to control the coagulation behavior and ensure its fluidity.

[0020] Furthermore, the reinforcing agent is an organosilicon powder.

[0021] The sand is quartz sand with a silicon dioxide content of ≥95%. Furthermore, the sand is made up of three grades: coarse, medium and fine, with a density of 2.4-2.7 g / m 3 .

[0022] Furthermore, the fiber is a fine steel fiber with a length of 8 to 13 mm, a diameter of 0.1 to 0.3 mm, and a yield strength of not less than 1400 MPa.

[0023] On the other hand, the present invention also provides a method for preparing the low-shrinkage ultra-high performance concrete, which specifically comprises the following steps:

[0024] (1) Mix cement, setting regulator, reinforcing agent, expansion agent, sand, fiber and mineral admixtures evenly, then add water and high-performance water reducer and stir for not less than 4 minutes;

[0025] (2) After the mixing is completed, the mixture described in step (1) is poured into a mold, and low shrinkage ultra-high performance concrete is obtained after molding and curing.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] (1) High-aluminum solid waste is co-fired with calcium oxide in an oxygen environment. On the one hand, the solid waste contains a high content of aluminum nitride, which can react to produce ammonia in the presence of water, which has adverse effects on both the environment and the durability of concrete. In this case, it is co-fired with calcium oxide at a certain temperature, so that the aluminum nitride is fully in contact with the oxygen in the environment, achieving the purpose of denitrification, thereby eliminating this adverse effect; on the other hand, during the co-firing process, the metallic aluminum in the high-aluminum solid waste is oxidized to aluminum oxide, and CaO can react with aluminum oxide or aluminum oxide and silicon dioxide. Under the quenching treatment, it is easy to form amorphous or glassy calcium aluminate, calcium aluminosilicate and other substances with certain reaction activity.

[0028] (2) By adding mineral admixtures, the larger specific surface area can optimize the particle grading of cementitious materials and improve the packing density of the slurry; at the same time, substances such as calcium aluminate and calcium aluminosilicate with certain reactivity can react with calcium hydroxide in the cement hydration product to generate hydrated calcium aluminosilicate. Compared with the hydrated calcium silicate product of ordinary Portland cement, the molecular chain is extended and the elastic modulus of the product is increased. This hydration product wraps the matrix and aggregate, improves the matrix-matrix and matrix-aggregate interface bonding strength, improves the microstructure of ultra-high performance concrete, and can improve the compressive strength while improving the tensile properties.

[0029] (3) A large proportion of high-aluminum solid waste replaces part of the cement and all of the silica fume in the existing ultra-high performance concrete, which greatly reduces the large chemical shrinkage caused by cement and silica fume during the hydration reaction and improves the volume stability of the matrix.

[0030] (4) The large amount of high-aluminum solid waste added not only optimizes the compressive strength, but also significantly reduces the cost of production and construction. At the same time, it proposes a method for the comprehensive utilization of solid and hazardous waste resources, providing another solution for the construction of environmentally friendly green ultra-high performance concrete. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0032] In each embodiment and comparative example, the cement is ordinary Portland cement with a strength grade of 52.5 produced by Jiangsu Helin Cement Co., Ltd., the high-performance water reducer is a PCA type water reducer produced by Jiangsu Subote New Materials Co., Ltd., the expansion agent is HME-Ⅲ produced by Jiangsu Subote New Materials Co., Ltd., and the sand density is 2.4-2.7 g / m 3 The quartz sand is made of 13mm long, 0.18mm diameter, and 1500MPa yield strength fine steel fiber. The setting agent is 99% high-purity industrial-grade sodium citrate. The reinforcing agent is a silicone powder defoamer produced by Jiangsu Subote New Materials Co., Ltd. Auxiliary cementitious materials such as coal-fired power plant bottom ash and coal gangue slag are provided by Nanjing Thermal Power Plant and Luxin New Building Materials Co., Ltd. Secondary aluminum ash and high-aluminum industrial waste slag are provided by Jiangsu Suzhou Chuanmao Metal Materials Co., Ltd.

[0033] Example 1

[0034] (1) Secondary aluminum ash, high aluminum industrial waste slag and CaO were mixed in a mass ratio of 1.5:0.5:1, mixed and co-fired at 850 ° C for 5 hours, taken out and placed in the air to quench and cool to room temperature, and then ground to an average particle size of not more than 5 μm and a specific surface area of ​​not less than 6000 m 2 / kg, and the mineral admixture is obtained.

[0035] (2) 100 parts of cement, 0.12 parts of setting agent, 2.5 parts of reinforcing agent, 5 parts of expansion agent, 100 parts of sand, 1.5 parts of fiber and 25 parts of mineral admixture were mixed uniformly by mass, and then 18 parts of water and 2.1 parts of high-performance water reducer were added and stirred for 5 minutes;

[0036] (3) After the mixing is completed, the mixture described in step (2) is poured into a mold, formed at 20°C, demolded after 24 hours, placed in a water curing box, and cured for 90 days under standard atmospheric pressure to obtain low shrinkage ultra-high performance concrete.

[0037] Example 2

[0038] (1) Secondary aluminum ash, coal-fired power plant bottom ash and CaO are mixed in a mass ratio of 1:0.5:1, mixed and co-fired at 900℃ for 4h, taken out and placed in air for rapid cooling to room temperature, and then ground to an average particle size of no more than 5μm and a specific surface area of ​​no less than 6000m 2 / kg, and the mineral admixture is obtained.

[0039] (2) 100 parts of cement, 0.14 parts of setting regulator, 2.8 parts of reinforcing agent, 7.1 parts of expansive agent, 114 parts of sand, 2.1 parts of fiber and 43 parts of mineral admixture were mixed uniformly by mass, and then 21.4 parts of water and 2.4 parts of high-performance water reducer were added and stirred for 5 minutes;

[0040] (3) After the mixing is completed, the mixture described in step (2) is poured into a mold, formed at 20°C, demolded after 24 hours, placed in a water curing box, and cured for 90 days under standard atmospheric pressure to obtain low shrinkage ultra-high performance concrete.

[0041] Example 3

[0042] (1) Mix secondary aluminum ash, coal gangue slag and CaO in a mass ratio of 1:0.6:1, and calcine them at 800℃ for 4.5h. Then take them out and quench them in air to room temperature. Then grind them to an average particle size of no more than 5μm and a specific surface area of ​​no less than 6000m 2 / kg, and the mineral admixture is obtained.

[0043] (2) 100 parts of cement, 0.16 parts of setting regulator, 3.3 parts of reinforcing agent, 8.3 parts of expansive agent, 133 parts of sand, 2.5 parts of fiber and 67 parts of mineral admixture were mixed uniformly by mass, and then 25 parts of water and 2.8 parts of high-performance water reducer were added and stirred for 5 minutes;

[0044] (3) After the mixing is completed, the mixture described in step (2) is poured into a mold, formed at 20°C, demolded after 24 hours, placed in a water curing box, and cured for 90 days under standard atmospheric pressure to obtain low shrinkage ultra-high performance concrete.

[0045] Example 4

[0046] (1) Secondary aluminum ash, coal gangue slag and CaO are mixed in a mass ratio of 0.9:0.9:1, mixed and co-fired at 860℃ for 4.5h, taken out and placed in the air to quench and cool to room temperature, and then ground to an average particle size of not more than 5μm and a specific surface area of ​​not less than 6000m 2 / kg, and the mineral admixture is obtained.

[0047] (2) 100 parts of cement, 0.2 parts of setting agent, 4 parts of reinforcing agent, 10 parts of expansive agent, 160 parts of sand, 3 parts of fiber and 100 parts of mineral admixture were mixed uniformly by mass, and then 30 parts of water and 3.5 parts of high-performance water reducer were added and stirred for 5 minutes;

[0048] (3) After the mixing is completed, the mixture described in step (2) is poured into a mold, formed at 20°C, demolded after 24 hours, placed in a water curing box, and cured for 90 days under standard atmospheric pressure to obtain low shrinkage ultra-high performance concrete.

[0049] Comparative Example 1

[0050] The low-shrinkage ultra-high performance concrete prepared in Comparative Example 1 is based on the setting of Example 1, the difference being that secondary aluminum ash and coal gangue slag are mixed in a ratio of 3:1, and mineral admixtures are added instead of the same mass. Other conditions are the same as those in Example 1.

[0051] Comparative Example 2

[0052] The low-shrinkage ultra-high performance concrete prepared in Comparative Example 2 is based on the setting of Example 1, the difference being that silica fume and bottom ash from a coal-fired power plant are mixed in a mass ratio of 1:1, and the mineral admixtures are replaced by equal mass. Other conditions are the same as those in Example 1.

[0053] Comparative Example 3

[0054] The low-shrinkage ultra-high performance concrete prepared in Comparative Example 3 is based on the setting of Example 1. The difference is that when preparing the mineral admixture, the secondary aluminum ash, coal gangue furnace and calcium oxide are co-fired, and then a slow cooling treatment is adopted instead of a sudden cooling treatment to obtain the mineral admixture for preparing the low-shrinkage ultra-high performance concrete. The other conditions are the same as those in Example 1.

[0055] Comparative Example 4

[0056] The low-shrinkage ultra-high performance concrete prepared in Comparative Example 4 is based on the setting of Example 1, the difference being that, when preparing the mineral admixture, the secondary aluminum ash and the bottom ash of the coal-fired power plant are replaced by the separate use of the bottom ash of the coal-fired power plant and co-fired with calcium oxide, and the other conditions are the same as those in Example 1.

[0057] Comparative Example 5

[0058] Comparative Example 5 is to further increase the amount of mineral admixture on the basis of Example 4 and adjust the content of other necessary phases. The details are as follows:

[0059] (1) Secondary aluminum ash, coal gangue slag and CaO are mixed in a mass ratio of 0.9:0.9:1, mixed and co-fired at 860℃ for 4.5h, taken out and placed in the air to quench and cool to room temperature, and then ground to an average particle size of not more than 5μm and a specific surface area of ​​not less than 6000m 2 / kg, and the mineral admixture is obtained.

[0060] (2) 100 parts of cement, 0.22 parts of setting agent, 5 parts of reinforcing agent, 5 parts of expansion agent, 200 parts of sand, 3 parts of fiber and 150 parts of mineral admixture were mixed uniformly by mass, and then 30 parts of water and 4.5 parts of high-performance water reducer were added and stirred for 5 minutes;

[0061] (3) After the mixing is completed, the mixture described in step (2) is poured into a mold, formed at 20°C, demolded after 24 hours, placed in a water curing box, and cured for 90 days under standard atmospheric pressure to obtain low shrinkage ultra-high performance concrete.

[0062] Performance Testing

[0063] The mechanical properties and shrinkage performance tests of the low-shrinkage ultra-high performance concrete prepared in Examples 1-4 and Comparative Examples 1-5 were performed; the mechanical properties test was carried out in accordance with the "GB / T 50081-2019 Standard for Test Methods for Physical and Mechanical Properties of Concrete"; the shrinkage performance test was carried out in accordance with the "GB / T50082-2009 Standard for Test Methods for Long-term Performance and Durability of Ordinary Soil Concrete".

[0064] Table 1 Mechanical properties and shrinkage performance test results of low shrinkage ultra-high performance concrete

[0065]

[0066] The results in Table 1 above show that by comparing Example 1 with Comparative Example 1, it can be found that Comparative Example 1 is a high-aluminum solid waste that is not co-fired with calcium oxide to replace the mineral admixture. Its 90d compressive strength is only 129.8MPa, the tensile strength is 15.6MPa, and the shrinkage is 550×10 -6 When the treated high-aluminum solid waste is added in an amount of 25 parts, the 90d compressive strength is 158.7MPa, the tensile strength is 22.8MPa, and the shrinkage is 423×10 -6The compressive strength increased by 13.5%, the tensile strength increased by 10.7%, and the shrinkage decreased by 23.1%, indicating that the internal addition of treated high-aluminum solid waste has a significant effect on improving the compressive and tensile strengths and reducing chemical shrinkage. The untreated solid waste contains a considerable amount of aluminum nitride, which reacts with water to generate ammonia. The gas that is not discharged in time leaves harmful holes in the hardened matrix, which is extremely detrimental to the development of mechanical properties.

[0067] Comparing Example 1 with Comparative Example 2, the silica fume and coal-fired power plant bottom ash in the existing common formula are replaced by mineral admixtures. The 90d compressive strength is increased by 2.0%, the tensile strength is increased by 8.0%, and the shrinkage is reduced by 27.7%, indicating that the replacement of mineral admixtures can greatly alleviate the great chemical shrinkage of the system caused by silica fume.

[0068] Comparing Example 1 with Comparative Example 3, in Comparative Example 3, high-aluminum solid waste was co-fired with calcium oxide at high temperature without quenching treatment. The original amorphous calcium aluminosilicate crystallized into calcium feldspar under slow cooling. The state of this substance is stable and its properties are stable in the pore solution under the cement hydration environment. Therefore, it only exists as a fine filler and has basically no optimization effect on the mechanical properties.

[0069] By comparing Example 1 with Comparative Example 4, the compressive strength of Example 1 mixed with composite high-aluminum solid waste is improved by 7.5%, the tensile strength is improved by 4.1%, and the shrinkage is similar compared with the single mixing of coal-fired power plant bottom ash. Example 1 mixed with high-aluminum solid waste shows great advantages.

[0070] By comparing Example 4 with Comparative Example 5, the excessive amount of mineral admixture was further increased on the basis of the original example. It was found that although the shrinkage of the concrete was greatly reduced, its compressive strength and tensile strength were significantly reduced compared with Example 4, and could not meet the ultra-high performance concrete standard. This is because, on the one hand, the large-scale replacement of the mineral admixture reduced the amount of cement and thus reduced the chemical shrinkage, but the extremely small amount of cement also reduced the amount of CS(A)-H gel generated in the matrix, and effective cross-linking could not be completely formed between the particles, thereby resulting in a decrease in mechanical properties.

[0071] In summary, the results of the examples and comparative examples show that the addition of a certain amount of mineral admixtures can optimize mechanical properties, reduce chemical shrinkage, and thus improve volume stability.

[0072] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A low shrinkage ultra-high performance concrete, characterized in that: The raw materials for its preparation include the following components by mass: The mineral admixture is a product of a quenching treatment after co-firing high-aluminum solid waste and CaO at 800-900°C.

2. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The high-aluminum solid waste is a mixture of secondary aluminum ash and one or more of coal-fired power plant bottom ash, high-aluminum industrial waste slag, and coal gangue slag, and the secondary aluminum ash accounts for no less than 30% of the total mass of the high-aluminum solid waste.

3. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The specific preparation method of the mineral admixture is: mixing high-aluminum solid waste and CaO at 800-900°C for 4-5h, taking out and placing in the air for rapid cooling to room temperature, and then grinding to an average particle size of not more than 5μm and a specific surface area of ​​not less than 6000m 2 / kg, the mineral admixture is obtained.

4. The low shrinkage ultra-high performance cement-based material according to claim 3, characterized in that: The mass ratio of the high-aluminum solid waste to CaO is 1.6-2.5:

1.

5. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The high-performance water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥35%.

6. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The expansion agent is a calcium oxide expansion agent, the setting agent is at least one of citric acid or sodium citrate, and the reinforcing agent is an organosilicon powder.

7. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The sand is quartz sand, and its silicon dioxide content is ≥95%.

8. The low shrinkage ultra-high performance concrete according to claim 7, characterized in that: The sand is made of three grades: coarse, medium and fine, with a density of 2.4-2.7 g / m 3 .

9. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The fiber is a fine steel fiber with a length of 8 to 13 mm, a diameter of 0.1 to 0.3 mm, and a yield strength of not less than 1400 MPa.

10. The method for preparing the low shrinkage ultra-high performance concrete according to any one of claims 1 to 9, characterized in that: The specific steps include: (1) Mix cement, setting regulator, reinforcing agent, expansion agent, sand, fiber and mineral admixtures evenly, then add water and high-performance water reducer and stir for no less than 4 minutes; (2) After the mixing is completed, the mixture described in step (1) is poured into a mold, and after molding and curing, a low shrinkage ultra-high performance concrete is obtained.

Citation Information

Cited By

  • Low-shrinkage high-toughness UHPC (Ultra High Performance Concrete) and impact property testing method thereof

    CN122520388A